Erratum: Computer Vision Syndrome Prevalence and Associated Factors Among the Medical Student in Kist Medical College - KC, Shiva Raj (Nepalese Medical Journal, 2019)
The online version of the “Computer Vision Syndrome Prevalence and Associated Factors Among the Medical Student in Kist Medical College”(Basnet A, Basnet P, Karki P, Shrestha S. Computer Vision Syndrome Prevalence and Associated Factors Among the Medical Student in Kist Medical College. Nep Med J. 2018;1:29-31. DOI: https://doi.org/10.3126/nmj.v1i1.20396 ) has been updated. In the publication, the study period was missed. The study period "from 2nd April 2018 to 15th April 2018" has been added. DOI: https://doi.org/10.3126/nmj.v1i1.20396